Evaluation of Students Satisfaction Factors on the Example of State and Private Universities - Ryńca, Radosław; Kuchta, Dorota (Ocena czynników satysfakcji studentów na przykładzie uczelni państwowej i uczelni prywatnych, 2011)
High competition on the educational market requires a proper approach to the university management. It seems necessary to evaluate a university also from the point of view of students themselves. The paper is devoted to the evaluation of the satisfaction of students in different areas of university functioning. The research was performed at three universities: one state and two private. It covered teaching process, university infrastructure and university reputation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 150-169
Keywords: student satisfaction; teaching process; university infrastructure; univeristy reputation